Cartography in dispute: the frontiers of Brazil in Abbé Raynal’s Histoire des Deux Indes - Junia Ferreira Furtado (Culture & History Digital Journal, 2021)
This article analyzes the frontier line(s) of Brazil proposed by the Portuguese ambassadors (D. Vicente de Sousa Coutinho, D. Rodrigo de Sousa Coutinho, and Luís de Sousa Coutinho, the Viscount of Balsemão), drawn on maps and documents sent to Abbé Raynal when he was preparing the 1780 edition of his famous Histoire des Deux Indes. This was accompanied by an Atlas de Toutes les Parties Connues du Globe Terrestre, produced by the French geographer Rigobert Bonne. The objective is, in light of the Treaty of Santo Ildefonso, to compare the lines defended by the ambassadors and those which Raynal and Bonne drew on the map of South America in the Atlas, analyzing the geopolitical impacts.